Reorganization of the Connectivity between Elementary Functions – A Model Relating Conscious States to Neural Connections - Mogensen, Jesper; Overgaard, Morten (Frontiers in Psychology, 2017)
In the present paper it is argued that the “neural correlate of consciousness” (NCC) does not appear to be a separate “module” – but an aspect of information processing within the neural substrate of various cognitive processes. Consequently, NCC can only be addressed adequately within frameworks that model the general relationship between neural processes and mental states – and take into account the dynamic connectivity of the brain. We presently offer the REFGEN (General Reorganization of Elementary Functions) model as such a framework. This model builds upon and expands the REF (Reorganization of Elementary Functions) and REFCON (Reorganization of Elementary Functions and Consciousness) models. All three models integrate the relationship between the neural and mental layers of description via the construction of an intermediate level dealing with computational states. The importance of experience based organization of neural and cognitive processes is stressed. The models assume that the mechanisms of consciousness are in principle the same as the basic mechanisms of all aspects of cognition – when information is processed to a sufficiently “high level” it becomes available to conscious experience. The NCC is within the REFGEN model seen as aspects of the dynamic and experience driven reorganizations of the synaptic connectivity between the neurocognitive “building blocks” of the model – the Elementary Functions.